2011
DOI: 10.1037/a0021662
|View full text |Cite
|
Sign up to set email alerts
|

Emotional reactivity to daily events in major and minor depression.

Abstract: Although emotional dysfunction is an important aspect of major depressive disorder (MDD), it has rarely been studied in daily life. Peeters, Nicolson, Berkhof, Delespaul, and deVries (2003) observed a surprising mood-brightening effect when individuals with MDD reported greater reactivity to positive events. To better understand this phenomenon, we conducted a multimethod assessment of emotional reactivity to daily life events, obtaining detailed reports of appraisals and event characteristics using the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
287
5
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(355 citation statements)
references
References 76 publications
61
287
5
2
Order By: Relevance
“…Lethbridge and Allen (2008) found that the absence of positive mood decrease following mood provocation was predictive of 12-month relapse. Recent studies on mood reactivity in depression highlight the role of daily stress as a provoking factor for mood reactivity and relapse in depressive symptomatology and highlight the role of measuring mood reactivity in daily life (Bockting et al, 2006;Britton et al, 2012;Bylsma, Taylor-Clift, & Rottenberg, 2011;Peeters et al, 2010;ten Doesschate et al, 2009). We speculate that patients who are highly reactive when confronted with a sad or very stressful event might be more susceptible to experiencing negative affect, in turn making them more vulnerable for relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Lethbridge and Allen (2008) found that the absence of positive mood decrease following mood provocation was predictive of 12-month relapse. Recent studies on mood reactivity in depression highlight the role of daily stress as a provoking factor for mood reactivity and relapse in depressive symptomatology and highlight the role of measuring mood reactivity in daily life (Bockting et al, 2006;Britton et al, 2012;Bylsma, Taylor-Clift, & Rottenberg, 2011;Peeters et al, 2010;ten Doesschate et al, 2009). We speculate that patients who are highly reactive when confronted with a sad or very stressful event might be more susceptible to experiencing negative affect, in turn making them more vulnerable for relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Participating in a meaningful, daily occupation has been shown to be especially important for people in such a situation, as through work, they can obtain positive experiences, like feeling needed, getting support and understanding, and having a purpose in daily life [6][7][8]. Previous studies have also shown that having an occupation leads to lessened symptoms of mental health disorders [9,10]. The main aim of mental health rehabilitation is to help individuals suffering from mental health disorders to develop the skills they require to live independent lives in the local community, with employment in vocational occupations as a vital element [11].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach is the Day Reconstruction Method (DRM), which asks participants to systematically reconstruct their experiences of the preceding day with procedures designed to reduce recall biases (Kahneman, Krueger, Sckade, Schwarz, & Stone, 2004). The DRM has been shown to have adequate test-retest reliability and high internal consistency (Bylsma, Taylor-Clift, & Rottenberg, 2011;Krueger & Schkade, 2008).…”
Section: Measuring Subjective Wellbeingmentioning
confidence: 99%